46 Indoleamine 2, 3-dioxygenase and cancerous inhibitor of pp2A expression and inflammation in lingual hyperplasia and tongue cancer. Issue 5 (May 2015) - Lehtinen, M.; Tervo, S.; Halme, E.; Tiilikainen, L.; Pohjola, K.; Honkanen, T.; Laranne, J.; Salmi, S.; Paavonen, T.
Abstract : Introduction: Tongue squamous cell carcinoma have poor survival rate and therefore new clinical biomarkers and therapeutics options are needed. Indoleamine 2, 3-dioxygenase (IDO) is an enzyme expressed in many cells involved in the catabolism of the essential amino acid tryptophan to kynurenine. Elevated IDO expression has been found in many tumors. Cancerous inhibitor of PP2A (CIP2A) is a protein which present in most human tissues. CIP2A is associated to high mortality rate in the tongue squamous cell carcinoma and in the other cancers. The objective of this study was to define the expression of IDO and CIP2A in tongue cancer and lingual mucosal hyperplasia, and evaluate the possible association of IDO and CIP2A expression and occurrence of regional metastasis in tongue cancer. In addition, we studied the effect of IDO expression, CIP2A expression and inflammation reaction of patient surviving. Materials and methods: We observed 94 patients that have been treated in Tampere University Hospital. Altogether 129 samples from the tongue squamous cell carcinomas ( n  = 64), lingual mucosa hyperplasia ( n  = 30) or regional lymph nodes ( n  = 35) were immunohistochemically stained with monoclonal antibodies anti-IDO and anti-CIP2A. The percentage of IDO positive cells indicating the IDO staining score, as well as IDO and CIP2A staining intensity were assessed in light microscopic evaluation. We also assessed the inflammation score of the samples. Results: There were a statistically significantly higher number of samples with IDO positivity in lingual hyperplasia group than in tongue cancer group. Moreover IDO staining intensity was higher in the hyperlplasia group, whereas the CIP2A staining intensity did not differ between hyperplasia than tongue cancer groups. Interestingly, the inflammation score was higher in the tongue cancer than in the hyperplasia tissue. When observing only the group with tongue cancer IDO expression was associated with poor survival. IDO staining intensity and staining score were stronger in higher TNM group and in higher tumor grades. Conclusion: Neither IDO nor CIP2A seem to be specific histological biomarkers for tongue cancer. Further direction of this study would be to observe whether inflammation process associates with the progression of tongue cancer.